Criteria for indication of initiation or discontinuation of life-sustaining therapy - Manna, Raffaele; Migliore, Alberto (Medicina e Morale, 1988)
Most of the ethical problems involved in life-support therapy may stem from a different understanding of authority in health care and a non-univocal interpretation of the principle of proportionality. Particularly in Anglo-Saxon circles, the theory is established that authority in medical care lies exclusively with patients or their legal representatives.